Muppets from space - Hill, Tim (Director); Henson, Brian; Baker, Martin G.; Juhl, Jerry; Mazzarino, Joseph; Kaufman, Kenneth; Tambor, Jeffrey, 1944-; Abraham, F. Murray; Arquette, David; Charles, Josh, 1971-; Hogan, Hulk, 1953-; Liotta, Ray.; et al. (Culver City, Calif. : Sony Pictures Home Entertainment, 2005)
When Gonzo's extraterrestrial relatives plan a visit, the government captures him in order to find out when his relatives will arrive.
Videodisc release of a 1999 motion picture production.
For specific features see interactive menu.
Produced by Brian Henson, Martin G. Baker ; written by Jerry Juhl, Joseph Mazzarino, Ken Kaufman ; music by Jamshied Sharifi.
Voices of the Muppets: Dave Goelz, Steve Whitmire, Bill Barretta and Frank Oz.
Jeffrey Tambor, F. Murray Abraham, David Arquette, Josh Charles, Hollywood Hogan, Ray Liotta, Andie MacDowell.
Rated G.
Keywords: Muppets (Fictitious characters) -- Juvenile drama; Life on other planets -- Juvenile drama; Muppets (Fictitious characters) -- Drama; Life on other planets -- Drama; Feature films; Children's films; Video recordings for the hearing impaired; Puppet films